The CAFTA-DR Free Trade Agreement — Analyzing its effects in a modern gravity framework - Juan René Rojas Rodríguez; Xenia Matschke (International Economics and Economic Policy, 2022)
We study the effects of the Dominican Republic–Central America–United States Free Trade Agreement (CAFTA-DR), signed in 2004, on the trade flows of its member states. Relying on the structural gravity model of trade framework, we find evidence of both increases and decreases in members' bilateral trade, but also of significant differences in these effects depending on the direction of trade and the trading members. Using a counterfactual analysis, we are also able to measure the general equilibrium effects of CAFTA-DR, finding that it has, in general, increased both total exports and income levels for El Salvador, Guatemala, Honduras, and Nicaragua. However, we also find evidence of sizable trade diversion and welfare losses for Costa Rica and the Dominican Republic.
Keywords: F14; F15; 330; Free trade agreements; Gravity model